2014
DOI: 10.2147/dnnd.s37353
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke cognitive impairment and dementia: prevalence, diagnosis, and treatment

Abstract: Three aspects of poststroke cognitive impairment and dementia are discussed in this review: prevalence; diagnosis; and treatment. The aim is to increase awareness of poststroke cognitive impairment in order to further stimulate strategies to recognize the condition and to prevent its progression. Approximately two-thirds of all middle-aged and elderly stroke patients develop cognitive impairment, and one in three develops dementia. The standard reference for diagnosis is a detailed neuropsychological examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 67 publications
4
23
0
3
Order By: Relevance
“…Our results support previous findings suggesting that EFs are highly susceptible to stroke-related impairments [23,24]. An extensive battery was used to examine which of the EF tests are able to detect stroke-related deficits in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…Our results support previous findings suggesting that EFs are highly susceptible to stroke-related impairments [23,24]. An extensive battery was used to examine which of the EF tests are able to detect stroke-related deficits in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…Acute post-stroke cognitive impairment (PSCI) is reported in up to 70% of patients [1]. While these deficits may improve within weeks/months after onset, over half of stroke survivors experience persisting long-term deficits, which can affect the daily functioning and quality of life [2].…”
Section: Introductionmentioning
confidence: 99%
“… 32 This study found a prior history of stroke to be more correlated with cognitive dysfunction, which is consistent with previous findings. 36 , 37 High cholesterol in particular has been found to be significant among females, and has been examined previously. 16 , 38 A recent study has found higher apolipoprotein e4-related risk of developing Alzheimer’s dementia in females, and this also partly accounts for the female preponderance with MCI.…”
Section: Discussionmentioning
confidence: 84%